ANALISA STRUKTUR MIKRO MATERIAL SS400 PADA PROSES PERLAKUAN PANAS METODE PACK CARBURIZING MENGGUNAKAN ARANG ENCENG GONDOK DARI DANAU LIMBOTO - Nurmala Shanti Dera; Onesimus Kevin Saputro; Novriyanti Talango (Asosiasi Dosen Muda Indonesia, 2024)
Water hyacinth is chosen as an environmentally friendly and abundant alternative carbon source. The test material, low-carbon steel SS400, is treated with pack carburizing heat treatment using water hyacinth charcoal as the carburizing medium. This study aims to analyze the effect of the pack carburizing method using water hyacinth charcoal from Lake Limboto on the microstructure of SS400 low-carbon steel. The analysis focuses on changes in the microstructure, hardness, and carbon distribution on the material's surface. The results show that the use of water hyacinth charcoal as a carburizing medium effectively increases the carbon content in the surface layer of the material, produces a martensitic microstructure after rapid cooling, and significantly improves surface hardness.